The application of the analytic hierarchy process in evaluating micro-computer simulation as a training and development method for a selected group of managers - Hendrikz, Johan de Sanderes (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1991.